(3GddGLFhf hGdbGfhf GdOhdj GdYGe (B/s - (3QGVj, Ydj QMjes ((3OeTb (B:s (3OGQ heDSSI QSdGf ddWHGYI hGdfTQ hGdJhRjY,s, 2018)
(3jHjf GdeDda BdjGJ GdMeGjI GdOhdjI ef MjK eG gj GdMeGjI, hef GdPj jMej GddGLF, hef ge GdTQcGA aj MeGjI GddGLFjf, CfhGY GddLhA hGSHGHg, GdfXGe GdbGfhfj hEdJRGeGJ GdgjFGJ GdOhdjI GdeNJUI HGddGLFjf hGdegGLQjf hGdEJaGbjGJ hGdbQGQGJ hGdEYdGfGJ GdOhdjI GdJj JYWj GddGLFjf GdVeGfGJ GdCMcGe GdNGUI HYOjej GdLfSj hef GdehVhYGJ GdegeI GdJj jJfGhdgG GdcJGH, GdaQb Hjf HdO GddLhA GdChd hHdO GddLhA GdKGfj, GfJgGA GddLhA, GdYhOI GdWhYjI, GdeahVjI GdSGejI dTDhf GddGLFjf, bjO SdWI GdOhdI aj CHYGO GddGLFjf, GdaQb Hjf GddGLF hGdegGLQ GdEbJUGOj, EJaGbjI TfZjf hEQJHGW HUeI TfZjf HHUeI OHdf, GdJTQjYGJ GdYQHjI hMeGjI GddGLFjf(B.s
(3HHdjhLQGajI (B: (3UaMI (B137-139.s
Keywords: (3GddGLFhf (B((3bGfhf Ohdj(B)s; (3GdbGfhf GdOhdjs